PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBINAAN AKHLAK KELAS V MADRASAH IBTIDAIYAH ATTAQWA 07 BEKASI - Novriwandi Novriwandi; Abdur Rahim (Bajang Institute, 2022)
This research was motivated by Madrasah Ibtidaiyah (MIS) Attaqwa 07 Tambun Bekasi as a formal religious institution. The uncontrolled behavior of children their age in urban environments is the reason for some parents' concern. However, with the congregational prayer schedule at MIS Attaqwa, it is hoped that students can develop better morals. This study aims to determine the role of Islamic Religious Education teachers as motivators, facilitators, educators as well as supporting and inhibiting factors in the moral development of fifth grade students of MIS ATTAQWA 07 Sriamur Tambun Utara, Bekasi Regency. This study uses a qualitative descriptive research methodology. The data collection techniques in this study were using in-depth interviews, observation and documentation. The results showed that the teacher's role as a motivator, included: (1) the teacher was always on time (2) the students were given material before the prayer was performed. (3) Giving encouragement (4) Motivating students. (5) Strengthen students' determination. The teacher's role as a facilitator includes (1) seeking learning resources. (2) provide services and facilities. (3) Helping students. (4) give encouragement. The teacher's role as an educator includes (1) Educating and teaching the importance of praying in congregation. (2) Directing students. (3) Teaching reading and prayer practice. (4) Consolidating student learning outcomes. (5) students know the content and values of congregational prayer.